PUL QIYMATINI IFODALOVCHI NUMERATIVLARNING PRAGMATIK XUSUSIYATLARI - Toirova, G.I.; Achilova, N.H. (SCIENCE and SOCIETY, 2022)
This state speech is about the pragmatics of the words of measurement studied in our linguistics, as well as about their history, place of consumption and scope. In addition, this country is considering a comparison of measurement words in the Uzbek language and arithmetic words in other languages. The state considers the number of words, pragmatic features of countable words that represent the meaning of money, and ix occurrence in speech. The pragmatic features of words that describe the value of money are that when they are used, the speech situation and the pragmatic approach in terms of determining conditions are mainly taken into account.